PELATIHAN TEKNIK MEMBACA EKSTENSIF DENGAN CEPAT DAN MUDAH UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA SMP SEKOLAH INDONESIA KUALA LUMPUR - Dwi Turistiani, Trinil; Suyatno; Ahmadi, Anas; Indarti, Titik; Permata Raharjo, Resdianto (ABIDUMASY, 2026)
This Community Service Activity (PKM) aims to improve the reading literacy skills of junior high school students at Sekolah Indonesia Kuala Lumpur through training in quick and easy extensive reading techniques. The training was conducted by a team of lecturers from the Indonesian Language and Literature Education Department of FBS Unesa, targeting 20 students from the Klang Malaysia Learning Center. The methods used included lectures, discussions, guided training, and mentoring. The training material covered the concepts of extensive reading, speed reading strategies, and effective text comprehension. Participants were given various texts on environmental themes and fables tailored to their age and abilities. After the reading training, students engaged in creative writing activities as a way to apply their reading comprehension skills. The results of the activity showed an increase in enthusiasm, motivation to read, and the ability to comprehend texts quickly. Most participants were able to produce creative writing based on their reading, although some students still required intensive mentoring due to their limited basic reading skills. The outputs of the activity included video documentation, mass media publications, scientific articles, and intellectual property rights certificates. Overall, this training was effective in fostering students' interest in reading and strengthening their literacy skills, and it is recommended to be continued with a sustainable mentoring program.